Simulation of Charge Sensitive Preamplifier using Multisim Software (International Journal of Current Engineering and Technology, 2015)
Simulation of the Charge Sensitive Preamplifier Circuit has been carried on Multisim Software. Multisim Software is powerful software that creates the best user friendly simulation environment for engineers, students and professors. We can simulate electronic circuits and generate prototype for Printed Circuit Boards (PCB’s). In this paper we have simulated the Charge Sensitive Preamplifier Circuit with a pulsed voltage source. We have analysed the behaviour of the Charge Sensitive Preamplifier Circuit with different rise times. The output waveforms have been observed on the oscilloscope.
Keywords: Multisim software; settling time; Charge Sensitive Preamplifier; decay constant